A Buddhist‐based meditation practice for care and healing: An introduction and its application. (26th April 2013) - Oshita, Daien; Hattori, Koji; Iwakuma, Miho
Abstract : This paper outlines Buddhist‐based meditation in terms of its spiritual, psychotherapeutic, physiological and neuroscientific perspectives. In the latter part of this paper, a pilot study is discussed, in which Japanese university students volunteered to practice meditation at home and complete questionnaires. T ‐tests were performed to compare with the non‐meditated control group. Although only a small number in the experimental group completed the study, our analyses demonstrated that students benefited from meditation and showed significant increases in their sense of coherence, self‐esteem and purpose in life. Lastly, practical implications of meditation in contemporary Japanese society are discussed.